Carbon Quantum Dots/Cu2O Heterostructures for Solar-Light-Driven Conversion of CO2 to Methanol - Li, Haitao; Zhang, Xinyi; MacFarlane, Douglas R. (Advanced energy materials, 2015)
A carbon quantum dots (CQDs)/Cu2O heterostructure with a protruding structure is synthesized and found to offer highly efficient photocatalytic conversion of CO2 to methanol under solar‐light irradiation. The CQDs/Cu2O photocatalyst exhibits excellent stability during the conversion process, which is attributed to the photoinduced electron transfer properties of the CQDs.